A Case Of Sustainability Reporting And Organisational Change In Practice Of Malaysian Palm Oil Company: Beyond The Symbolic And Substantive Dichotomy - Ahmad, Saidatul Nurul Hidayah Jannatun Naim Nor (2020)
The concept of sustainable business practice and reporting have taken centre stage in the global consumer products supply chain and sourcing decision specifically with the widespread prevalence of environmental and social violations in the palm oil industry. The purpose of this study is to explore the institutional pressures and changes in sustainability reporting and practice made in respond to these pressures by a Malaysian public listed company in the palm oil sector. Case study methodology was employed, gathering primary and secondary data through semi-structured interview, observation, informal conversation, focus group discussion and content analysis. Neo-institutional, legitimacy and impression management theory were used as the lens to explain the study findings. The findings show there are both external and internal pressures/motivation for company to embark on sustainability reporting and practices. Externally, stakeholder pressure mainly came from the NGOs and competitors that puts pressure on the multinational buyers, investors and financiers whom in turn place pressure on the case company, making it highly effective, as it risked the company’s financial bottom lines. Regulatory pressures, conforming to industry norms, and seeking support of foreign government also increases the external pressures. Reputational problems and labour shortages, business case for sustainability and philanthropic nature of family-owned firm are the internal motivation behind the endeavour.